(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article explores the impact of environmental consciousness on cognitive development, emphasizing its psychological and educational significance. It examines how fostering environmental consciousness enhances problem-solving skills, critical thinking, and ethical decision-making. Additionally, the study investigates how educational systems can integrate environmental awareness into curricula to cultivate responsible and engaged citizens. The findings indicate that embedding ecological education in learning processes improves cognitive abilities and promotes sustainable behavior.